2021
DOI: 10.3390/ijms22083935
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Link between Obesity and Prostate Cancer

Abstract: Obesity is a pandemic of increasing worldwide prevalence. There is evidence of an association between obesity and the risk of prostate cancer from observational studies, and different biologic mechanisms have been proposed. The chronic low-level inflammation within the adipose tissue in obesity results in oxidative stress, activation of inflammatory cytokines, deregulation of adipokines signaling, and increased circulating levels of insulin and insulin-like growth factors (IGF). These mechanisms may be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Indeed, miR-107 also allowed a strong discriminatory capacity between SigPCa and NonSigPCa in obese PCa patients, thus representing not only a diagnostic but also a potential prognostic biomarker in that an obesity condition has been reported to represent a risk factor for PCa development, aggressiveness, and mortality. 43,44 Altogether, our results provide new, compelling evidence supporting the contention that miR-107 represents a promising diagnostic, prognostic, and/or therapeutic tool, worth to be further explored, in the pathological association between PCa and obesity.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, miR-107 also allowed a strong discriminatory capacity between SigPCa and NonSigPCa in obese PCa patients, thus representing not only a diagnostic but also a potential prognostic biomarker in that an obesity condition has been reported to represent a risk factor for PCa development, aggressiveness, and mortality. 43,44 Altogether, our results provide new, compelling evidence supporting the contention that miR-107 represents a promising diagnostic, prognostic, and/or therapeutic tool, worth to be further explored, in the pathological association between PCa and obesity.…”
Section: Discussionsupporting
confidence: 56%
“…This state leads to decreased cancer cell apoptosis and increased cancer cell growth and migration. Thus, these multiple factors may work in tandem to create a favorable tumor microenvironment for PCa cell growth in the catheter ( 34 ). Obesity has also been associated with insulin and sex hormone levels as well as the insulin-like growth factor axis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms connecting adiposity and the progression of PC are poorly understood, and may be multifactorial[ 40 ]. In this respect, prospective components consisting of adipokine signaling pathways, sex hormone concentrations, and variation along the insulin/insulin-like-growth-factor (IGF) axis were involved[ 41 42 ]. (1) In adipokine signaling pathways, leptin and adiponectin are the two most plentiful and well-studied adipokines.…”
Section: P Ossible Mechanisms Connecting Obesity and Prosta...mentioning
confidence: 99%
“…Insulin increases cell proliferation and glucose consumption in PC cells but not in noncancerous prostate epithelial cells[ 55 ]. The IGF-axis is composed of cell surface receptors, ligands, IGF-binding proteins, and proteases[ 41 ]. Epidemiological studies have shown that higher serum IGF-1 concentrations and downregulated circulating IGFBP-3 levels are correlated with an increased risk of developing PC[ 56 ].…”
Section: P Ossible Mechanisms Connecting Obesity and Prosta...mentioning
confidence: 99%